The Utilization of Digital Flashcard in English Vocabulary Learning at Elementary School - Ronal Saputra; Maulina Maulina; Rahmat Nasrullah (Jurnal Pendidikan Indonesia, 2025)
In Indonesia’s elementary education, English vocabulary acquisition remains challenging due to limited exposure and traditional methods. Digital flashcards, recognized for their interactivity and accessibility, offer a potential solution, yet their efficacy in low-resource settings is underexplored. This study investigates the effectiveness of Canva-based digital flashcards in enhancing vocabulary comprehension among Grade I students at SD Negeri 50 Kendari, a school with minimal English proficiency. A pre-experimental one-group pretest-posttest design was employed with 24 students. Pretest and posttest data (10 multiple-choice questions) were analyzed using SPSS 16.0, including paired samples t-tests (α = 0.05). Results showed a significant increase in mean scores from 21.25 (pretest) to 46.25 (posttest) (p = 0.000), confirming digital flashcards’ effectiveness. However, external factors (e.g., motivation) were noted as limitations. The study underscores digital flashcards’ utility in resource-constrained contexts and advocates for further research on long-term retention, multimodal integration, and adaptive technologies. Practical contributions include a replicable model for teachers using Canva to create low-cost, engaging materials.